Optimalisasi Pengelolaan Operasional Petshop Berbasis Visual Studio - Fajarwati, Ayu Naila; Rohmah, Nafa Ur Roisatu; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
The increasing demand for efficient and accurate management in petshop operations has highlighted the limitations of traditional methods. This study aims to develop and evaluate a digital solution,